Comparative assessment of UV-C radiation and non-thermal plasma for inactivation of foodborne fungal spores suspension in vitro - Kulišová, Markéta; Rabochová, Michaela; Lorinčík, Jan; Maťátková, Olga; Brányik, Tomáš; Hrudka, Jan; Scholtz, Vladimír; Jarošová Kolouchová, Irena (RSC advances, 2024)
Fungal contamination poses a persistent challenge to industries, particularly in food, healthcare, and clinical sectors, due to the remarkable resilience of fungi in withstanding conventional control methods. In this context, our research delves into the comparative efficacy of UV radiation and non-thermal plasma (NTP) on key foodborne fungal contaminants - Alternaria alternata, Aspergillus niger, Fusarium culmorum, and Fusarium graminearum. The study examined the impact of varying doses of UV radiation on the asexual spores of all mentioned fungal strains. Simultaneously, the study compared the effects of UV radiation and NTP on the metabolic activity of cells after spore germination and their subsequent germination ability. The results revealed that UV-C radiation (254 nm) did not significantly suppress the metabolic activity of cells after spore germination. In contrast, NTP exhibited almost 100% effectiveness on both selected spores and their subsequent germination, except for A. niger. In the case of A. niger, the effectiveness of UV-C and NTP was nearly comparable, showing only a 35% decrease in metabolic activity after 48 hours of germination, while the other strains (A. alternata, F. culmorum, F. graminearum) exhibited a reduction of more than 95%. SEM images illustrate the morphological changes in structure of all tested spores after both treatments. This study addresses a crucial gap in existing literature, offering insights into the adaptation possibilities of treated cells and emphasizing the importance of considering exposure duration and nutrient conditions (introduction of fresh medium). The results highlighted the promising antimicrobial potential of NTP, especially for filamentous fungi, paving the way for enhanced sanitation processes with diverse applications.